2012
DOI: 10.1002/jms.2038
|View full text |Cite
|
Sign up to set email alerts
|

Improved sample preparation of glyphosate and methylphosphonic acid by EPA method 6800A and time‐of‐flight mass spectrometry using novel solid‐phase extraction

Abstract: The employment of chemical weapons by rogue states and/or terrorist organizations is an ongoing concern in the United States. The quantitative analysis of nerve agents must be rapid and reliable for use in the private and public sectors. Current methods describe a tedious and time-consuming derivatization for gas chromatography-mass spectrometry and liquid chromatography in tandem with mass spectrometry. Two solid-phase extraction (SPE) techniques for the analysis of glyphosate and methylphosphonic acid are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…Various methods have been used to compensate for or eliminate matrix effects, such as additional clean‐up steps, performing matrix‐matched calibration or using an extrapolative dilution approach . Occasionally, isotope‐labeled glyphosate and AMPA standards have been used in analyses with MS and MS/MS, which eliminate concerns of incomplete elution from SPE cartridges, sorbent effects and MS drift …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods have been used to compensate for or eliminate matrix effects, such as additional clean‐up steps, performing matrix‐matched calibration or using an extrapolative dilution approach . Occasionally, isotope‐labeled glyphosate and AMPA standards have been used in analyses with MS and MS/MS, which eliminate concerns of incomplete elution from SPE cartridges, sorbent effects and MS drift …”
Section: Discussionmentioning
confidence: 99%
“…However, to conduct the necessary research, simple, sensitive methods of analysis are required for glyphosate and AMPA in water, plant materials and soil samples. In addition to the environmental applications of such methods, it has been suggested that methods developed for glyphosate can be used for analysis of chemical weapons such as phosphonic acid‐containing nerve agents for which glyphosate has been used as a surrogate . While numerous reliable and sufficiently sensitive analytical techniques used to quantify glyphosate have been published since its introduction, they are, for the most part, rather complex and time consuming in order to compensate for glyphosate's chemical properties (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate glyphosate research, simple, sensitive methods of analysis are needed for glyphosate in water, plant and soil samples. In addition, it has been suggested that the simple, sensitive methods developed for glyphosate can be used for analysis of chemical weapons such as phosphonic‐acid‐containing nerve agents; glyphosate has been used as a surrogate for these chemicals …”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been suggested that the simple, sensitive methods developed for glyphosate can be used for analysis of chemical weapons such as phosphonic-acid-containing nerve agents; glyphosate has been used as a surrogate for these chemicals. 2 Numerous analytical techniques used to quantify glyphosate have proven to be reliable and sufficiently sensitive for most purposes. However, most of the methods are rather complex and time consuming, which leads to numerous 'new' or 'revised' methods being reported every year in the literature for water, plants or soil.…”
Section: Introductionmentioning
confidence: 99%
“…22 This mass bias factor was applied as a correction factor to the isotope signals in the IDMS equation, as given by the following equation: 10 Samples of 4.0 mL of the mixture of working solutions containing both natural and isotopically enriched analytes at 20.0 ng mL À1 were analyzed (n ¼ 28) to determine mean signal intensities for each natural and each isotopic analyte.…”
Section: Mass Bias Factormentioning
confidence: 99%